Stochastic Optimal Operation for Integrated Energy System Considering Multiple Uncertainties - Li, Chengao; Pu, Yue; Gao, Yukun; Liu, Haoming (2022 IEEE 3rd China International Youth Conference on Electrical Engineering (CIYCEE), 2022)
Given uncertainties of distributed generation (DG) output and multi-energy loads including electricity, heating, and cooling in integrated energy systems (IES), an IES stochastic optimal operation strategy considering multiple uncertainties of source-side and load-side is proposed in the paper. Firstly, through analyzing the influences of multiple uncertainties, the stochastic optimization model of IES is established. Then, with the sample average approximation (SAA), the stochastic optimization model is converted into a deterministic mixed-integer linear programming model and solved by the CPLEX solver. Finally, the feasibility of the proposed strategy is verified through an example, and sensitivity analysis of different fluctuation degrees and uncertainty factors is further carried out. Compared with the traditional deterministic model, the proposed stochastic optimization model is more in line with reality.